Low-energy universality in three-body models - Delfino, A.; Frederico, T.; Tomio, L. [UNESP] (Springer Nature, 2000)
We study the low-energy universality observed in three-body models through a scale-independent approach. From the already estimated infinite number of three-body excited energy states, which happen in the limit when the energy of the subsystem goes to zero, we are able to identify the lower energies of the helium trimers as possible examples of Thomas-Efimov states. By considering this example, we illustrate the usefulness of a scaling function, which we have defined. The approach is applied to bosonic systems of three identical particles, and also to the case where two kinds of particles are present.